Rancang Bangun Website Himpunan Mahasiswa Bontang Wilayah Kampus Makassar - Adelia Puspita Hilal; Muhammad Sofyan Daud Pujas; Chindy Febryan Erwana Putri; Isty Hamdayani; Eliyah A M Sampetoding; Edy Saputra Rusdi; Esther S Manapa (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
The Bontang Student Association (HMB) is a regional student organization originating from the City of Bontang, East Kalimantan. By measuring the development of the times that are visible today, designing a system with the right analytical techniques using technology as the foundation will be something that is able to capture the walls that limit everyone's thinking. Therefore, using the website as a forum for gathering thoughts in concluding a solution is the right application of technology for the regional organization. HMB is an organization that functions as a forum for developing the quality and quality of its cadres. To carry out this task, an event was held at this organization in order to gather all the opinions of the scattered cadre representatives to respond to the social problems under review. Solving problems encountered byan organization certainly requires the right solution for the thoughts of its members to be collected and more efficient. So in this service case studywe are trying to design a website to facilitate service to the organization.